Report dose-to-medium in clinical trials where available; a consensus from the Global Harmonisation Group to maximize consistency. (June 2021) - Kry, Stephen F.; Lye, Jessica; Clark, Catharine H.; Andratschke, Nicolaus; Dimitriadis, Alexis; Followill, David; Howell, Rebecca; Hussein, Mohammad; Ishikawa, Masayori; Kito, Satoshi; Kron, Tomas; Lee, Jonny; et al.
Highlights: Dm, m, Dw, w, and Dw, m are all used in clinical practice. To maximize clinical trial impact and interpretability, a single consistent framework is preferred. The GHG recommends using Dm, m when available. Abstract: Purpose: To promote consistency in clinical trials by recommending a uniform framework as it relates to radiation transport and dose calculation in water versus in medium. Methods: The Global Quality Assurance of Radiation Therapy Clinical Trials Harmonisation Group (GHG; www.rtqaharmonization.org ) compared the differences between dose to water in water ( Dw, w ), dose to water in medium ( Dw, m ), and dose to medium in medium ( Dm, m ). This was done based on a review of historical frameworks, existing literature and standards, clinical issues in the context of clinical trials, and the trajectory of radiation dose calculations. Based on these factors, recommendations were developed. Results: No framework was found to be ideal or perfect given the history, complexity, and current status of radiation therapy. Nevertheless, based on the evidence available, the GHG established a recommendation preferring dose to medium in medium ( Dm, m ). Conclusions: Dose to medium in medium ( Dm, m ) is the preferred dose calculation and reporting framework. If an institution's planning system can only calculate dose to water in water ( Dw, w ), this is acceptable.